Feasibility and acceptability of a midwife-led intervention programme called 'Eat Well Keep Active' to encourage a healthy lifestyle in pregnancy - Jaynie Rance (BMC pregnancy and Childbirth, 2012)
Eating a diet that is high in fat and sugar and having a sedentary lifestyle during pregnancy is understood to increase the risk of excessive gestational weight gain and obesity following the birth of the baby. However, there are no clinical guidelines in the UK on what is considered to be appropriate gestational weight gain. Clinical recommendations discourage the routine weighing of pregnant women, stating that women should be advised regarding their diet and activity levels, in order to prevent excessive weight gain. Pregnancy is seen as a time when many women may have an increased motivation to improve their lifestyle behaviours for the benefit of the fetus. However, it is evident that many women have difficulty in both maintaining a healthy balanced diet and remaining active through pregnancy. It would seem that midwives may be ideally placed to assist women to make and maintain healthier lifestyle choices during pregnancy. This study will look at the feasibility and acceptability of a newly devised intervention programme called 'Eat Well Keep Active'. Participants will complete a questionnaire prior to the programme to obtain baseline data on food frequency, physical activity and to gauge their perception of personal ability to improve/maintain healthy lifestyle. The programme comprises client centred techniques; motivational interviewing and goal setting delivered early in pregnancy (12-16 weeks) with the aim of supporting a healthy well balanced diet and either continuing or commencing appropriate levels of physical activity. Participants will then be followed up six weeks following the intervention with a one-to-one interview, and a further brief questionnaire. The interview will provide preliminary data regarding perceived effectiveness and acceptability of the 'Eat Well Keep Active' programme whilst the questionnaire will provide data regarding changes in the confidence of participants to lead a healthy lifestyle.